WELFARE AND INCOME DISTRIBUTION EFFECTS OF MINIMUM WAGE IN NIGERIA (2015)
The primary motive of a minimum wage policy is to provide a wage floor for low income earners and improve their welfare. In Nigeria, real minimum wage declined by 83.0% between 1974 and 2010, thus lowering the welfare of workers. Low skilled relative to high skilled workers’ wages also declined from 29.0% in 1991 to 11.0% in 2007. While there is a growing body of literature on the direct effects of minimum wage, there have been little attempts to investigate its indirect welfare and income distribution effects. This study, therefore, investigated the indirect welfare and income distribution effects of minimum wage in Nigeria. Monopsonistic competition provided the theoretical framework, while a static computable general equilibrium model, based on the Walrasian theory of market behaviour was adopted. The model analysed the welfare and income distribution effects of minimum wage on households as it captured changes in wages, income, labour demand, consumption, and commodity prices. The model was calibrated using a 2006 Social Accounting Matrix (SAM). The SAM has ten sectors, six household categories (low, middle, high rural households, low, middle, and high urban households) and four labour categories; (formal skilled and unskilled, informal skilled and unskilled). Welfare was captured using equivalent variation measure, while Gini coefficient and Theil entropy were used to measure income inequality. Four sets of scenarios (20.0%, 35.0%, 50.0% and 140.0% wage increases), based on historical wage reviews in Nigeria were simulated over the ₦7,500 per month minimum wage in effect till 2011. Employment of minimum wage workers declined by 123.0%, indicating the direct effect of the minimum wage increase. The indirect effect manifested in employers substituting labour from the informal sector for the expensive minimum wage labour, thus putting upward pressure on the wage rates in the informal sector. The consumer price index also increased by 52.0%. In the 20.0%, 35.0% and 50.0% simulations, only high-urban households recorded an improvement in welfare of 0.007, 0.014 and 0.021 respectively based on the equivalent variation measure. The largest welfare losses which ranged from -0.066 to -0.090 were registered by low-rural, low-urban, and middle rural households (lower income households). Middle-urban and high-rural households’ welfare improved relatively with an increase in the minimum wage. In the 140.0% simulation, equivalent to ₦18,000 minimum wage approved in 2011, high-urban, middle-urban, and high-rural households (upper income households) had welfare improvement, while low-rural, middle-rural, and low-urban households showed no improvement. Income distribution improved as minimum wage increased, with Gini index and Theil entropy income inequality measures declining from 0.43 to 0.40, and 0.08 to 0.07 respectively. The minimum wage policy reduced income inequality, but only the welfare of the upper income households improved. Minimum wage policies worsen the welfare of its intended beneficiaries, due to negative impact on prices and employment. Complementary welfare policies targeted at the unskilled and informal sector workers should be pursued simultaneously with the minimum wage to assuage the negative effects.